2000
DOI: 10.1128/jb.182.4.1144-1149.2000
|View full text |Cite
|
Sign up to set email alerts
|

Crc Is Involved in Catabolite Repression Control of the bkd Operons of Pseudomonas putida and Pseudomonas aeruginosa

Abstract: Crc (catabolite repression control) protein of Pseudomonas aeruginosa has shown to be involved in carbon regulation of several pathways. In this study, the role of Crc in catabolite repression control has been studied in Pseudomonas putida. The bkd operons of P. putida and P. aeruginosa encode the inducible multienzyme complex branched-chain keto acid dehydrogenase, which is regulated in both species by catabolite repression. We report here that this effect is mediated in both species by Crc. A 13-kb cloned DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 33 publications
(22 reference statements)
4
99
0
Order By: Relevance
“…Inactivation of the crc gene relieved the repression of a number of genes implicated in the metabolism of carbohydrates and nitrogenated compounds in Pseudomonas aeruginosa and P. putida (Collier et al, 1996;Hester et al, 2000a).…”
Section: Operons Affected By the Repression In A Baylyimentioning
confidence: 99%
“…Inactivation of the crc gene relieved the repression of a number of genes implicated in the metabolism of carbohydrates and nitrogenated compounds in Pseudomonas aeruginosa and P. putida (Collier et al, 1996;Hester et al, 2000a).…”
Section: Operons Affected By the Repression In A Baylyimentioning
confidence: 99%
“…1 In nonenteric Gram-negative bacteria, such as Pseudomonas, general induction of hut expression is not well understood. Succinate-induced catabolite repression (based solely on enzyme activity assays) has been reported (Hug et al 1968;Phillips and Mulfinger 1981), although no role has been found for the global regulatory proteins Crc (catabolic repression control; Hester et al 2000) and Vfr (virulence factor regulator, which is homologous to the E. coli CAP protein; Suh et al 2002). Recent work has shown the involvement of a newly discovered two-component regulatory system, CbrAB (Nishijyo et al 2001;Zhang and Rainey 2007).…”
mentioning
confidence: 99%
“…The levels and activity of Crc vary depending on growth conditions [231] and it has also been reported to inhibit the expression of many other catabolic pathways for several non-preferred compounds in Pseudomonads [230,[232][233][234][235][236][237].…”
Section: Catabolite Repression Controlmentioning
confidence: 99%